ECONOMIC EFFECTS OF TRADE POLICY ADJUSTMENTS IN THE WORLD MARKET FOR JAPONICA RICE - 이현옥 (Univ. of California, Davis., 2006)
World agricultural markets are entering another key period of policy adjustment as the Doha Development Agenda negotiation is being finalized. This paper investigates likely global market effects of expansion of access into the market in Japan and Korea and reduced subsidy for japonica rice in the United States. Using an equilibrium displacement model, we simulate changes in market prices, quantities and other aggregates in the presence of policy shocks. Results show that when U.S. subsidies decrease by 50 percent in addition to the full implementation of quota expansion in Korea and Japan, U.S. production decreases by more than 30 percent, and the U.S. is no longer an exporter. Instead, China increases its exports by 53 percent. The rest of the world increases exports by 14 percent and the world price rises by 0.7 percent. Changes in the Korean market are modest. Since Korea imports solely on the basis of its quota schedule, the Korean rice market is not connected to the world market, and these quotas remain relatively small compared to the size of the Korean market. The rice price in Korea decreases by 1.3 percent and production falls by 3.9 percent.
Keywords: Policy adjustment; japonica rice; world rice market; market access; subsidy; Policy adjustment; japonica rice; world rice market; market access; subsidy